2004
DOI: 10.1029/2003jd004292
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight transmission through desert dust and marine aerosols: Diffuse light corrections to Sun photometry and pyrheliometry

Abstract: [1] Desert dust and marine aerosols are receiving increased scientific attention because of their prevalence on intercontinental scales and their potentially large effects on Earth radiation, climate, other aerosols, clouds, and precipitation. The relatively large size of dust and marine aerosol particles produces scattering phase functions that are strongly forward peaked. Hence Sun photometry and pyrheliometry of these aerosols are more subject to diffuse light errors than is the case for smaller aerosols. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…However, this is a minor issue in the visible range and only accounts for few percentage points when the largest aerosol particles (e.g. desert dust) are to be measured, as calculated by Russell et al (2004).…”
Section: Mkiv Brewer-specific Contributors To Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is a minor issue in the visible range and only accounts for few percentage points when the largest aerosol particles (e.g. desert dust) are to be measured, as calculated by Russell et al (2004).…”
Section: Mkiv Brewer-specific Contributors To Uncertaintymentioning
confidence: 99%
“…Furthermore, the measuring spectral range of MkIV Brewers nicely overlaps with the operating wavelengths of other sun photometers, thus avoiding the need of extrapolations in order to compare different kind of instruments. Finally, measuring AOD in the blue band is, in principle, simpler than in the UV, since several instrumental issues, such as the effects of spectral stray light, finite bandwidth (Slusser et al, 2000) and diffuse radiation entering the field of view (FOV) due to the aerosol forward scattering peak (Russell et al, 2004), are reduced at larger wavelengths. Therefore, a better understanding of AOD retrieval in the visible range may be a first step and a useful test bench towards improving AOD estimates at smaller (and more demanding) wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…This relatively small FOV ensures that the instrument is less sensitive to atmospheric scattering into the FOV than instruments with broader FOV. The effect of atmospheric forward scattering on direct solar irradiance measurements increases with particle size, aerosol optical depth and instrument FOV; it has been shown that the impact is negligible (less than 1 % of AOD) for FOV smaller than 2 • (Russell et al, 2004). A more recent study (Sinyuk et al, 2012) confirms that in most cases for a CIMEL-like instrument, this effect can be neglected excepted for heavy dust loadings where the relative error may reach ∼ 1 % for an AOD of 3.5.…”
Section: Description Of the Instrumentmentioning
confidence: 99%
“…The MFRSR AODs were corrected to match the Cimel AODs following a method similar to that described in Russell et al (2004). This allows the construction of a corrected data set that extends throughout the AMF deployment period, rather than just the limited time period when the Cimel was operational.…”
Section: Discussionmentioning
confidence: 99%
“…To correct the MFRSR AODs, we devise a scheme similar to that presented in Russell et al (2004), for which the correction depends on the Angstrom exponent as a proxy for the aerosol size. For large Angstrom exponents (smaller particles), the correction is small, and the magnitude of the correction increases as the Angstrom exponent decreases (larger particles).…”
Section: Correcting the Mfrsr Aerosol Optical Depth Retrievalsmentioning
confidence: 99%